2010
DOI: 10.1002/ajhb.21056
|View full text |Cite
|
Sign up to set email alerts
|

The role of fat mass index in determining obesity

Abstract: Objective To compare body mass index (BMI), percent body fat (PBF), and fat mass index (FMI) and to investigate the accuracy of FMI as a convenient tool for assessing obesity. Design Anthropometric measurements and bioelectrical impedance analyses were performed on 538 Mexican Americans (373 women and 165 men). Correlations between BMI and PBF and between FMI and PBF were investigated. The percentage of persons misclassified as obese using different classifications was calculated. Multiple linear regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
109
3
12

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(132 citation statements)
references
References 64 publications
8
109
3
12
Order By: Relevance
“…Reports indicated that a large proportion of boys and girls has misperception about their weight status. 5 Boys were likely than girls to classify their weight status lower than their weight status determined by actual BMI, hence, considered as underestimation of weight status. Whereas girls were more likely to classify their weight status higher than their actual weight status measured with BMI which considered as overestimation of weight status 8 .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Reports indicated that a large proportion of boys and girls has misperception about their weight status. 5 Boys were likely than girls to classify their weight status lower than their weight status determined by actual BMI, hence, considered as underestimation of weight status. Whereas girls were more likely to classify their weight status higher than their actual weight status measured with BMI which considered as overestimation of weight status 8 .…”
Section: Introductionmentioning
confidence: 98%
“…Among the factors is body image, and body size perception is among body image interests, which has been studied in relation to obesity [4][5][6][7][8] . A number of studies have examined levels of overestimation and underestimation of body size in youths compared to their actual body size obtained from e.g.…”
Section: Introductionmentioning
confidence: 99%
“…11 These BMI percentiles have excellent sensitivity for the identification of children most at risk for the health-related consequences of obesity and are easily applied in clinical practice. Among typically developing children, body fat distribution rather than the total body mass may have a greater impact on cardiovascular risk, 15,16 but body composition measurement by methods such as DXA cannot practically be applied as a screening measure in clinical practice. Currently, BMI is the easiest and best…”
Section: Figurementioning
confidence: 99%
“…Peltz et al concluded that the discrepancies between the BMI and PBF were due to the BMI's limitations [41]. There are criticisms associated with the BMI [42], including its frequent misclassification [43], high rate of false negatives, and that it cannot be in a standard form.…”
Section: Discussionmentioning
confidence: 99%